Una nueva especie de alacrán del género Centruroides Marx (1890) (Scorpiones, Buthidae) de la depresión del Balsas, México - Ponce Saavedra, Javier; Francke, Oscar F. (Instituto de Ecología, A.C., 2020)
A new species of scorpion of the genus Centruroides Marx is described. It occurs in the Balsas River Depression in the states of Guerrero and Michoacan, Mexico, at elevations ranging from 400 m to 1500 m above sea level. It has eight rows of denticles on the pedipalp fingers, and belongs to the stripped section of the genus, where it had been previously confused with Centruroides limpidus limpidus Karsch and with Centruroides limpidus tecomanus Hoffmann. It differs in morphometrics and color pattern. The new species is sympatric with C. limpidus limpidus in the eastern part of its range in the state of Michoacan, and with Centruroides infamatus Pocock in the Sierra de Coalcoman and adjacent regions in the northern part of the state. One locality in Guerrero State and another one in Mexico State are recorded too.